2006
DOI: 10.1192/bjp.bp.105.019307
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of second-generation antipsychotics and haloperidol in acute schizophrenia

Abstract: Haloperidol, olanzapine and risperidone are superior to aripiprazole, quetiapine and ziprasidone for the acute treatment of psychosis in hospitalised patients with schizophrenia, schizoaffective disorder or schizophreniform disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
33
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 25 publications
6
33
2
2
Order By: Relevance
“…In the present study, the treatment response in the haloperidol group was smaller than has generally been observed in other short-term studies of schizophrenia that used the BPRS [Adams et al 2013;Beasley et al 1996;McCue et al 2006]. Similarly, adjusted mean BPRS change scores in the lurasidone-treatment groups were generally smaller than those in the other phase II studies of lurasidone for schizophrenia [Nakamura et al 2009;Ogasa et al 2013].…”
Section: Discussioncontrasting
confidence: 51%
“…In the present study, the treatment response in the haloperidol group was smaller than has generally been observed in other short-term studies of schizophrenia that used the BPRS [Adams et al 2013;Beasley et al 1996;McCue et al 2006]. Similarly, adjusted mean BPRS change scores in the lurasidone-treatment groups were generally smaller than those in the other phase II studies of lurasidone for schizophrenia [Nakamura et al 2009;Ogasa et al 2013].…”
Section: Discussioncontrasting
confidence: 51%
“…However, a more recent trial compared oral risperidone solution monotherapy with oral olanzapine tablets and found equal efficacy in successfully reducing acute agitation (Hatta 2008). One ambitious study compared five atypical antipsychotics with each other and demonstrated superior efficacy of olanzapine and risperidone over quetiapine, ziprasidone and aripiprazole for the acute treatment of schizophrenia, schizoaffective disorder or schizophreniform disorder (McCue 2006). Another study, conducted in an emergency room, found olanzapine and risperidone to be superior in efficacy to quetiapine in treating acute psychosis (Raja 2003).…”
Section: Efficacymentioning
confidence: 99%
“…However, despite their undeniable utility, they do not fully reproduce the clinical benefits of clozapine, and therapeutic indexes to doses eliciting undesirable actions are limited; in particular, EPS for risperidone and obesity for olanzapine (Dean and Scarr, 2004;Lieberman et al, 2005;Margolese et al, 2005). Moreover, although the more recently launched partial dopaminergic agonist, aripiprazole, is well tolerated, its efficacy is not superior to that of other agents (Abi-Dargham and Laruelle, 2005;Burstein et al, 2005;McCue et al, 2006;Urban et al, 2007b). Clearly, there remains a need for innovative drugs possessing improved efficacy and favorable side-effect profiles.…”
mentioning
confidence: 99%
“…Furthermore, clozapine elicits sedation, obesity, cardiovascular-autonomic, and metabolic side effects via actions at ␣ 1 -adrenoceptors (ARs), histamine (H 1 ) receptors, and muscarinic receptors (Cunningham-Owens, 1996;Millan et al, 2000a;Pacher and Kecskemeti, 2004). A number of other multireceptorial antipsychotics have been introduced with similar, although not identical, broad-based receptorbinding profiles: notably, olanzapine and risperidone (Millan et al, 2000a;Dean and Scarr, 2004;Lieberman et al, 2005;McCue et al, 2006). However, despite their undeniable utility, they do not fully reproduce the clinical benefits of clozapine, and therapeutic indexes to doses eliciting undesirable actions are limited; in particular, EPS for risperidone and obesity for olanzapine (Dean and Scarr, 2004;Lieberman et al, 2005;Margolese et al, 2005).…”
mentioning
confidence: 99%